Meningeal inflammation is widespread and linked to cortical pathology in multiple sclerosis - Owain Howell (Brain, 2011)
Meningeal inflammation in the form of ectopic lymphoid-like structures has been suggested to play a prominent role in the development of cerebral cortical grey matter pathology in multiple sclerosis. The aim of this study was to analyse the incidence and distribution of B cell follicle-like structures in an extensive collection of cases with secondary progressive multiple sclerosis with a wide age range and to determine their relationship to diffuse meningeal inflammation, white matter perivascular infiltrates and microglial activation. One hundred and twenty three cases with secondary progressive multiple sclerosis were examined for the presence of meningeal and perivascular immune cell infiltrates in tissue blocks and/or whole coronal macrosections encompassing a wide array of brain areas. Large, dense, B cell-rich lymphocytic aggregates were screened for the presence of follicular dendritic cells, proliferating B cells and plasma cells. Ectopic B cell follicle-like structures were found, with variable frequency, in 49 cases (40) and were distributed throughout the forebrain, where they were most frequently located in the deep sulci of the temporal, cingulate, insula and frontal cortex. Subpial grey matter demyelinated lesions were located both adjacent to, and some distance from such structures. The presence of B cell follicle-like structures was associated with an accompanying quantitative increase in diffuse meningeal inflammation that correlated with the degree of microglial activation and grey matter cortical demyelination. The median age of disease onset, time to disease progression, time to wheelchair dependence and age at death all differed significantly in these cases when compared with those without B cell follicle-like structures. Our findings suggest that meningeal infiltrates may play a contributory role in the underlying subpial grey matter pathology and accelerated clinical course, which is exacerbated in a significant proportion of cases by the presence of B cell follicle-like structures.